Phase equilibrium data on binary and ternary mixtures of methyl palmitate, hydrogen and propane - Rovetto, Laura Jorgelina (2004)
The hydrogenolysis of fatty acid methyl esters (FAME) to obtain fatty alcohols, is a catalytic, multiphase reaction. Reaction rates can be greatly increased by using a supercritical solvent to bring the reactive mixture into a single homogeneous phase. Knowledge of the corresponding phase equilibria is a prerequisite in order to find the homogeneous region and to determine the most favorable conditions for the hydrogenation process. This paper reports experimental phase equilibrium data on binary and ternary mixtures of methyl palmitate, hydrogen and propane. A temperature region between 360 and 450 K, and pressures up to 15 MPa were covered.